The mechanism of irisin via Nrf2/GPX4 signaling pathway in alleviating lipopolysaccha-ride-induced acute lung injury in rats - Jing LUO; Jun PENG; Jing ZHANG; Yun WANG; Xin-Yi LI (Yixue xinzhi zazhi)
Objective To study the role of Nrf2/GPX4 signaling pathway in irisin alleviating lipopoly-saccharide (LPS)-induced acute lung injury in rats.Method Seventy-two healthy male SD rats were ran-domly divided into control group (C group), acute lung injury group (ALI group), irisin group (Ir group), irisin+Nrf2 inhibitor group (Ir+ML385 group). 24 hours after the model preparation, bronchoalveolar lavage fluid (BALF) was collected for protein concentration determination, and the contents of IL-6 and TNF-α in BALF were detected by ELISA. Pathologic results of lung tissue sections were observed by HE staining and scored, and the wet/dry weight ratio of the lung tissue was calculated. The contents of Fe2+, MDA and GSH in lung tissue homogenate were detected by colorimetric method. The protein levels of GPX4, ACSL4 and nuclear Nrf2 in lung tissues were determined by western blot (WB).Result Compared with the control group, the protein contents in BALF, the IL-6 and TNF-α contents, lung pathological in-jury score, wet/dry weight ratio, the contents of Fe2+ and MDA were increased, the GSH content and GPX4 level were decreased, the protein levels of ACSL4 and nuclear Nrf2 were increased in ALI group (P